Crystal structure of (E)-1-{2-[(5, 5-dimethyl-1, 3, 2-dioxaphosphinan-2-yl)oxy]naphthalen-1-yl}-N-(4- fluorophenyl)methanimine. (January 2015) - Said, Musa A.; Belewi, Bayan L. Al; Hughes, David L.
No abstract available